(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
This study was carried out to determine the total content of flavonoids of dried and fresh hawthorn flowers and leaves in water and hydroalcolic extracts. The method of cold and hot maceration was used to prepare these extracts. The active compounds which were found in these extracts were detected by many chemical reactions. The results of these tests showed that the extracts contain: phenols, flavonoids, and saponins.The total content of flavonoids was determined using spectrophotometric methods by forming complex with aluminum chloride and measurement absorbance at 510nm, it has been shown that quantity of flavonoids in dried samples ranges from 0.16 to 1%, while it’s quantity in fresh samples 0.026- 0.18%.